DESIGN AND MAKING HOMEPAGE PT. EMBOSSINDO UTAMA USING HOMESITE 5.2 - Frans Gunawan; Susi Wagiyati P, SKom, MM (Jurnal Sistem Informasi, 2000)
Designing and Making Homepages PT. Embossindo Utama Using Homesite 2.5. Inaccordance with its title, the author discusses how to create a simple homepagebegins with making the structure of the homepage, making plans to manufacture thehomepage. On the steps of manufacture described making the homepage so thatreaders understand how making this homepage.Basically, the purpose of making this homepage is to introduce to readers how thebasics of making the homepage by using the program homeSite.